POLYTYPE DISTRIBUTION OF CIRCUMSTELLAR SILICON CARBIDE: MICROSTRUCTURAL CHARACTERIZATION BY TRANSMISSION ELECTRON MICROSCOPY - Daulton T.L.; Bernatowicz T.J.; Messenger S.; Stadermann F.J.; Amari S.; Lewis R.S. (My University, 2003)
Silicon carbide (SiC) is a particularly interesting species of presolar grain because it is known to form on the order of a hundred different polytypes in the laboratory, and the formation of a particular polytype is sensitive to growth conditions. Astronomical evidence for the formation of SiC in expanding circumstellar atmospheres of asymptotic giant branch (AGB) carbon stars is provided by infrared (IR) studies. However, identification of the crystallographic structure of SiC from IR spectra is controversial. Since >95% of the presolar SiC isolated from meteorites formed around carbon stars, a determination of the structure of presolar SiC is, to first order, a direct determination of the structure of circumstellar SiC. We therefore determined the polytype distribution of presolar SiC from the Murchison CM2 carbonaceous meteorite using analytical and high-resolution transmission electron microscopy (TEM). High-resolution lattice images and electron diffraction of 508 individual SiC grains demonstrate that only two polytypes are present, the cubic 3C ({beta}-SiC) polytype (79.4% of population by number) and the hexagonal 2H ({alpha}-SiC) polytype (2.7%). Intergrowths of these two polytypes are relatively abundant (17.1%). No other polytypes were found. A small population of one-dimensionally disordered SiC grains (0.9%), whose high density of stacking faults precluded classification as any polytype, was also observed. The presolar origin of 2H {alpha}-SiC is unambiguously established by tens-of-nanometers-resolution secondary ion mass spectroscopy (NanoSIMS). Isotopic maps of a TEM-characterized 2H {alpha}-SiC grain exhibit non-solar isotopic compositions of {sup 12}C/{sup 13}C = 64 {+-} 4 and {sup 14}N/{sup 15}N = 575 {+-} 24. These measurements are consistent with mainstream presolar SiC thought to originate in the expanding atmospheres of AGB carbon stars. Equilibrium condensation calculations together with inferred mineral condensation sequences predict relatively low SiC condensation temperatures in carbon stars. The laboratory observed condensation temperatures of 2H and 3C SiC are generally the lowest of all SiC polytypes and fall within the predictions of the equilibrium calculations. These points account for the occurrence of only 2H and 3C polytypes of SiC in circumstellar outflows. The 2H and 3C SiC polytypes presumably condense at different radii (i.e., temperatures) in the expanding stellar atmospheres of AGB carbon stars.